2017
DOI: 10.1016/j.scitotenv.2016.12.118
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analogies in microbial communities in natural drinking water biofilms

Abstract: Biofilms are ubiquitous throughout drinking water distribution systems (DWDS), playing central roles in system performance and delivery of safe clean drinking water. However, little is known about how the interaction of abiotic and biotic factors influence the microbial communities of these biofilms in real systems. Results are presented here from a one-year study using in situ sampling devices installed in two operational systems supplied with different source waters. Independently of the characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 38 publications
7
63
0
Order By: Relevance
“…These results, together with the observed shapes and the high alkalinity of the water averaging 162 mg/L as CaCO 3 (Table 2), suggest the presence of copper carbonates on the surface. It has been reported that malachite (Cu(OH) 2 CuCO 3 ) has a passivating effect on the copper surface [7,25]. The passivation characteristics of malachite would explain the increments of open circuit potential (OCP) values and the lower corrosion rate shown in the samples exposed for eight months (shown later).…”
Section: Scanning Electron Microscopymentioning
confidence: 93%
See 4 more Smart Citations
“…These results, together with the observed shapes and the high alkalinity of the water averaging 162 mg/L as CaCO 3 (Table 2), suggest the presence of copper carbonates on the surface. It has been reported that malachite (Cu(OH) 2 CuCO 3 ) has a passivating effect on the copper surface [7,25]. The passivation characteristics of malachite would explain the increments of open circuit potential (OCP) values and the lower corrosion rate shown in the samples exposed for eight months (shown later).…”
Section: Scanning Electron Microscopymentioning
confidence: 93%
“…However, the microbial contamination in the source water of the system did not pose a problem in observing the microbial changes occurring on the inner wall of copper pipes. The changes in the bulk water communities do not exert an evident influence on the composition of the attached community, as discussed by Douterelo et al [2]. Another approach considered a dilution effect owing to a previous rain event; however, this effect was discarded because it did not feature the same change trend in all measured parameters.…”
Section: Water Qualitymentioning
confidence: 99%
See 3 more Smart Citations